Effectiveness of chemical disinfection on biofilms of relined dentures: A randomized clinical trial - Moffa, Eduardo B.; Izumida, Fernanda E. [UNESP]; Jorge, Janaina H. [UNESP]; Mussi, Maria C. M.; Siqueira, Walter L.; Giampaolo, Eunice T. [UNESP] (Mosher & Linder, Inc, 2016)
Purpose: To evaluate the effect of disinfection with sodium perborate or chlorhexidine (when combined with brushing) on the removal of biofilm in relined dentures. Methods: Swabs were collected 48 hours after the relining procedure and at the follow-up time intervals of 7, 15, 30, 90, and 180 days. The dentures' surface roughness was measured at the same times. 45 subjects were randomly divided into three groups of 15 subjects each. The control group brushed with coconut soap and a soft toothbrush. The sodium perborate group followed the same procedure and also disinfected with sodium perborate solution for 5 minutes per day. The chlorhexidine group followed the control group procedure and disinfected with 2% chlorhexidine digluconate solution for 5 minutes per day. The number of colony forming units and the surface roughness were evaluated statistically by 2-way repeated-measure ANOVA (alpha = 0.05). Results: The control group dentures exhibited similar levels of microbial cells throughout the experiment. However, after 15 days, no microbial growth was observed on the dentures for which either disinfection agent was used. There were no statistically significant differences in superficial roughness between the groups (P = 0.298). The disinfection agents used, combined with brushing, were able to remove the relined dentures' biofilm after 15 days of disinfection. Roughness was not a predominant factor in CFU reduction.